An Android based private haji agency locator mobile application / Aina Syafiqa A Lazim - A Lazim, Aina Syafiqa (2022)
Hajj is a fadhilat for all Muslims. So, it is important to be equipped and practised. The purpose of this mobile application is to assist the user in finding nearby private Hajj agencies, giving and keeping notes on Hajj and Umrah. The objectives of this project are to identify, design, develop, and demonstrate the Private Hajj Agency Locator mobile application. This mobile application was developed using Android Studio and Firebase as development software. An analysis of the literature review had been done before the system was developed. Other than that, to develop this mobile application, the Mobile Application Development Life Cycle (MADLC) method until the testing stage has been applied. Moreover, from the results and findings, it is clear that this mobile application functioned well, but there were some features that needed to be improved. For future work and recommendations, the developer can add recommendation features and provide the mobile application in a Malay language version.